PTH-219 Prevalence of intestinal failure-associated liver disease within a home parenteral nutrition service. (22nd June 2015) - Fitzpatrick, M; Evans, A; De Silva, A
Abstract : Introduction: Intestinal failure-associated liver disease (IFALD) is a potentially life-threatening and historically common complication of long-term parenteral nutrition. In the past two decades advances in catheter sepsis prevention and the development of novel lipid formulations have reduced the prevalence of IFALD. We examined the point prevalence of surrogate markers of IFALD within the home parenteral nutrition (HPN) service at the Royal Berkshire Hospital. Method: The records of the HPN service were examined to identify patients receiving HPN between January 2012 and December 2014. Clinic notes, electronic patient records and imaging results were used to extract clinical information. Results: Twenty-four patients (13 male; mean age 60 years, range 21–83 years) received long-term home parenteral nutrition during the study period for a mean duration of 25 months (range 3–54 months). Underlying causes of intestinal failure included inflammatory bowel disease (7, 29%), vascular causes (5, 21%), surgical complications including fistulae, sepsis and adhesions (5, 21%), malignancy (4, 17%) and dysmotility (3, 12%). Most patients received a tailor-made PN bag 3–7 days a week (median 5 days a week) with a lipid emulsion (SMOF) bag twice a week. In this cohort 16 patients had persistently abnormal liver biochemistry (raised ALT and/or ALP greater than the reference range for longer than six months). Two patients had mildly elevated bilirubin (1–2 x upper limit of normal). There were no clinical presentations of decompensated liver disease. Nineteen patients had hepatic imaging (ultrasound or CT) during the study period. One patient had splenomegaly secondary to portal vein thrombosis and one patient had ascites related to Budd-Chiari syndrome. No other patients had radiological signs of portal hypertension or cirrhosis on imaging. Three patients underwent transient elastography measurement (Fibroscan ® ) one of which had an elevated reading (10.7kPa, IQR 1.5). Conclusion: These results show that two thirds of patients on long-term parenteral nutrition had persistent abnormalities in liver biochemistry which may indicate steatohepatitis. No patients showed signs of cirrhosis on imaging or presented with decompensated liver disease during the three-year study period. Whilst this is a relatively short follow-up period to detect the development of chronic liver disease, previous studies have reported a prevalence of complicated liver disease of 26% after two years of PN. 1 We plan to prospectively monitor liver biochemistry, abdominal imaging and transient elastography in our HPN cohort to assess the natural history of IFALD. Disclosure of interest: None Declared. Reference: Cavicchi M et al . Prevalence of liver disease and contributing factors in patients receiving home parenteral nutrition for permanent intestinal failure. Ann Intern Med. 2000;132:525–532